Rural China from modernization to reconstruction - Sit, Tsui (Asian Studies, 2013)
Chinese rural society has played a significant role in the modernization, industrialization, and economic development of the People’s Republic of China from the 1950s onwards, albeit at great cost. This process was characterized by, among others, the siphoning of resources away from the rural areas; the ongoing expropriation of land; human and environmental degradation; the erosion of local enterprises in the name of export-oriented growth; and the undercutting of local governance. Rural China has also absorbed the attendant crises— massive unemployment, among others—that have been generated by the country’s economic policies. Despite the fate that has befallen rural China, it will and should continue to play a role in the future developmental trajectory of the country. It is in this light that the historical and contemporary manifestations of rural reconstruction movements in China, which are based on the small peasantry and village community, provide an alternative to destructive modernization. This will ensure the protection of rural livelihoods and function as a resistance hub to the external crisis derived from global capitalism.